PENGETAHUAN DAN SIKAP REMAJA DENGAN PERILAKU SEKSUAL SISWA SEKOLAH MENGAH ATAS - Brigitte Inez Maitimo; Dismo Katiandagho (Jurnal Kesehatan Lingkungan, 2018)
Adolescents entering the transitional period, have less knowledge about premarital sexual relations. Premarital sexual attitudes of adolescents can be influenced by many things, apart from knowledge factors also influenced by cultural factors, mass media, personal experiences, educational institutions, religious institutions and emotions within individuals. Sexual behavior in adolescents can be manifested in various behaviors, ranging from feelings of attraction, dating, holding hands, kissing cheeks, hugging, kissing lips, holding breasts, holding genitals and doing intercourse. The aim of the study was to find out the relationship between the level of knowledge and attitudes of adolescents with sexual behavior in SMA 1 Gemeh. The type of research used is analytical with approach cross sectional, with a sample of 54 respondents using purposive sampling technique. The results of the research data were analyzed using test Chi Square. The results of data analysis prove that the highest presentation for the level of knowledge is the respondent with a good level of knowledge and good behavior, and the highest attitude is the respondent with a positive attitude and good sexual behavior. Conclusion, no there is a relationship between the level of knowledge with sexual behavior, there is no relationship between adolescent attitudes and sexual behavior. Suggestions, for teachers in the school to provide assistance for students to increase their knowledge and attitudes about sexual behavior.